(untitled) (Khairulummah, 2024)
Sufism, which is fundamentally based on self-purification, spiritual training, and closeness to Allah, faces various challenges in the modern era. Some contemporary claimants of Sufism have deviated from its true essence, incorporating innovations, extremism, materialistic motives, and un-Islamic rituals. Consequently, misconceptions have arisen among the masses, causing Sufism to lose its original effectiveness and purpose. In the light of the Seerah of the Prophet Muhammad ﷺ, solutions to these issues can be found, demonstrating that true Sufism aligns strictly with the teachings of the Quran and Sunnah. The life of the Prophet ﷺ exemplified piety, sincerity, moderation, and exemplary moral conduct. He emphasized spiritual development within the framework of Islamic teachings and never encouraged exaggeration or the adoption of un-Islamic practices. This research will explore how contemporary claimants of Sufism can seek guidance from the Prophet’s ﷺ Seerah to realign themselves with authentic Sufi principles. Furthermore, it will analyze possible reforms, such as adherence to the Quran and Hadith, moral and spiritual purification, and rejecting innovations. By doing so, this study aims to restore modern Sufism to its true essence, ensuring its alignment with the fundamental teachings of Islam.